Global green port development models and the assessment of their applicability: A Case study of Vietnam’s Southern ports - Thi Anh Tho, Tran; Thi Bich Ngoc, To; Nguyen Thai Hoang, Lam; Huy Nhat Tai, Le (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2025)
With 80% of international trade transported by sea, maritime transport serves as the tool through which society navigates the dynamic interaction of supply and demand, featuring its critical role in global commerce. The shipping industry is under growing pressure from current International Maritime Organization (IMO) policies aimed at reducing the impact of climate change and heading towards the bright future of sustainability. Although the maritime industry recognizes green ports as a crucial solution to environmental pollution and climate issues, the progress of green port development, particularly in developing countries, remains limited. Vietnam is making significant efforts to develop environmentally friendly ports, with a vision towards 2050 of connecting the dry port systems with logistics hubs, expecting to serve the increasing demand of container transport and other logistics businesses in numerous localities. However, there are some obstacles to getting everything done properly. This study aims to identify the key factors in building and developing green port models from leading countries in the industry by comparing the differences in port construction and formulation among major designated ports in the world and notable representatives of Vietnam. After that, the study shall assess the hypothesis of applying green port development models in Vietnam in line with global trends. Our research also highlights the support and encouragement for green port initiatives from the government, indicating Vietnam’s significant potential in constructing and developing green port models. Additionally, the study figures out current disadvantages and significant challenges in coping with these movements in the future.